Bhaktapur Tourism - Badal, Bharat Prasad (Research Nepal Journal of Development Studies, 2020)
Development in this age of sustainable development is sustainable development itself and tourism development is sustainable development of tourism. The present paper investigates the development of tourism from the socio economic indicators of sustainable tourism of Bhaktapur. Bhaktapur is an open museum and central hub of Tourism. To explore the Economic dimension of Bhaktapur Sustainable Tourism Development through Employment that focuses Number, type and duration of jobs, Gender equity, Business viability, Expenditure, Arrivals, Profitability, and Satisfaction. And to analyze the Social dimension of Bhaktapur Sustainable Tourism Development through Quality of Life that focuses Resident Empowerment, Congestion and crowding, Community attitudes to tourism, Access to amenities, and Changes in crime rate, the study has been conducted. The primary information is based on multiple sources of societal learning like field visits in course of doing researches, observation of various sites, General Household Questionnaire Survey, focus on group discussions, interactive seminars and a number of interactions and interviews with the experts of tourism sector in Bhaktapur. General Household Questionnaire Survey of purposively selected cluster of Dattatraya Square area was conducted on 157 households. Among five clusters Dattatrya Square was purposely selected for the study. Actual spending and length of stay of foreign tourists have been increasing in Nepal. Altogether from socio economic perspective 13 programsare recommended from the study to the local government of Bhaktapur Dattatrya. It needs around265 lakhs and timeline is not more than one year. Five times of these 13 projects and 265 lakhs can double the visitors in coming years.